Scientific and methodological tools of cost management of enterprises: the main approaches and proposals - M. S. Dikunova (Статистика и экономика, 2017)
A study of the economic nature of expenses for the industrial and defense enterprises occurs through the definition of a conceptual framework, harmonization of definitions of such things as cost, costs and expenses. In the study, these concepts are used as equivalent terms. In theory, there are different classifications of production cost and sales of products’ cost, a part of which is not used in practice. While analyzing the legislative division into elements it was proposed to complement the legal classification of an element of the costs of supply and distribution. The need for categorization is obvious, which is possible after considering the existing classifications of expenditures in the completely manufacturing process. This study shows that they do not solve all the tasks by the cost control. This problem can be solved if you set the relationship of costs and revenues with the actions of the persons, responsible for the use of resources and introduce so-called responsibility centers.The most promising methods include: cost-benefit analysis, planning on a zero basis, strategic cost management in the organization. The comparative analysis allowed to create the fundamental basis for their combined use in the creation of a mechanism to control costs, because this method is widely used in recent times by progressive enterprises. However, there are problems of its implementation with regard to the current economic situation in the state.The law regulates supply and marketing policy of the companies. The analysis of the used classifications in the supply and marketing systems of the enterprises allowed offering group costs. Their elements are described in detail and delimitation of the production costs is carried out. There is no such a division in practical activities of enterprises.To confirm this fact and clarify further research directions, we have considered the real status of the expenses for manufacture and realization of production and analyzed the functionality of the system of supply and distribution that helped to create an element base for our study.In addition, the structural parts of the supply and marketing systems are defined that need to work in the process of cost management in industrial and defense industries.It was found that for creation of the effective, scientific-methodical instrument of cost management for supply and distribution it is necessary to study the main approaches, identifying the strengths and weaknesses of each. Besides, principles and methods are different when functioning of the strategic and operational levels of the management costs.Thus, the solution of the scientific task will be to study and develop the scientific methodology of cost management in industrial enterprises and enterprises of the military-industrial complex, essential for the solution of problems of pricing and optimization of production processes.